2006
DOI: 10.1071/sr05188
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of crop rotation, stubble management and tillage on soil phosphorus dynamics

Abstract: The effects of various management practices on soil phosphorus (P) dynamics were investigated in a field experiment in New South Wales, Australia, during 24 years of different crop rotation, stubble management, and tillage treatments. Topsoil samples collected at the beginning of the trial and after 6, 12, 18, and 24 years were analysed for resin-extractable P, inorganic and organic P, and total P. According to the calculated P input-output budget, 9-14 of the 20 kg P/ha added as superphosphate annually remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 31 publications
4
35
2
Order By: Relevance
“…The higher C and N budgets in the treatment WS-M-D were due to N 2 fixation, mulch retention and direct drilling, while the lowest budget reported for WW-B-C was due to regular cultivation, absence of significant N 2 fixation, and mulch burning. The P budgets were positive as reported by Bünemann et al (2006). The C and N budgets derived from Heenan et al (2004) were significantly correlated with each other (p < 0.05; Table S6) and both budgets were significantly correlated with the P budget calculated in this study (p < 0.05; Table S6).…”
Section: C N P Inputs and Budgets In The Wagga Wagga Trialsupporting
confidence: 65%
“…The higher C and N budgets in the treatment WS-M-D were due to N 2 fixation, mulch retention and direct drilling, while the lowest budget reported for WW-B-C was due to regular cultivation, absence of significant N 2 fixation, and mulch burning. The P budgets were positive as reported by Bünemann et al (2006). The C and N budgets derived from Heenan et al (2004) were significantly correlated with each other (p < 0.05; Table S6) and both budgets were significantly correlated with the P budget calculated in this study (p < 0.05; Table S6).…”
Section: C N P Inputs and Budgets In The Wagga Wagga Trialsupporting
confidence: 65%
“…Vu et al 58 found a concentration of plant-available P in 0-10 cm under NT. A high accumulation of C org was closely related to organic P dynamics, as organic P accumulates only when C availability is high 59 . Plantavailable K in the top layer was greater under RT, whereas there were no differences between RT and ploughed soil in 10-20 cm 5 .…”
Section: Phosphorus and Potassiummentioning
confidence: 99%
“…Concentrations of resin-extractable P were high and not yield-limiting for annual crops (Cantarella et al 1998), which can be explained by 26 years of continuous P fertilisation. Thus, the higher annual wheat grain yield during the first 24 years of the trial in the wheat-lupin and wheat-subclover rotations (3.7-4.0 tons ha −1 ) compared to continuous wheat (2.2 tons ha −1 ) can be attributed, at least partly, to improved nitrogen supply in rotations including legumes (Bünemann et al 2006). The increase in total P in all treatments compared to 1979 confirmed the measured change in total P in the top 20 cm during the first 24 years of the trial (Bünemann et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the trial have been published in a number of publications addressing wheat and lupin yields (Heenan et al 1994(Heenan et al , 2000 and various soil properties (Chan and Heenan 1993;Chan et al 2002;Heenan and Chan 1992;Heenan et al 2004;Heenan and Taylor 1995). Soil P dynamics during the first 24 years of the trial have been described by Bünemann et al (2006).…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation